Cyclic swell–shrink behaviour of an expansive soil treated with a sulfonated oil. Issue 3 (17th August 2022) - Soltani, Amin; Raeesi, Ramin; O'Kelly, Brendan C.
Abstract : The effects of a sulfonated oil (SO) stabiliser on the swell–shrink properties of an expansive soil were investigated through cyclic wetting–drying tests. The cyclic wetting–drying action led to the reconstruction of the soil microstructure by inducing clay particle aggregation. Accordingly, the greater the number of applied cycles, the lower the swell–shrink potential up to the fourth cycle, beyond which the swelling and shrinkage strains attained elastic equilibrium. At any given cycle, the tendency for swell–shrink reduction was in favour of the SO concentration up to 0·75%, beyond which the excess SO molecules self-associated in the form of aggregates, thereby acting as a 'lubricant' rather than a clay-stabilising agent. As a result of SO treatment, the accumulated axial strain progressively transitioned towards a desirable, 'neutral' state, with 0·75% SO exhibiting the highest resistance against cyclic wetting–drying. For any given SO concentration, the equalised void ratio–moisture content curves for wetting and drying followed the same S-shaped path, further corroborating that the swelling and shrinkage processes, on achieving elastic equilibrium, become reversible. The shrinkage and liquid limits indicated a progressive transition towards a desirable, aggregated fabric, with 0·75% SO identified as the optimum concentration.